Injuries by marine and freshwater stingrays: history, clinical aspects of the envenomations and current status of a neglected problem in Brazil - Junior,Vidal Haddad (2013)
Stingrays are a group of rays – cartilaginous fish related to sharks – that have whiplike tails with barbed, usually venomous spines and are found around the world, especially the marine species. Despite recent reports of accidents involving these fish, they are not aggressive, reacting only when stepped on or improperly handled. Injuries by stingrays are seldom mentioned by historians, although they have always been present in riverine communities of inland waters and in South American coasts. Indeed, envenomations by stingrays are quite common in freshwater and marine fishing communities. Although having high morbidity, such injuries are neglected because they have low lethality and usually occur in remote areas, which favor the use of folk remedies. In the present review article, historical aspects of injuries caused by stingrays in Brazil and their distribution on the coast of São Paulo state and riverine communities of the North, Midwest and Southeast regions were studied. In addition, other aspects were analyzed such as clinical features, therapeutic methods, preventive measures and trends in occurrence of these accidents in the country, particularly in areas in which freshwater stingrays had not been previously registered, being introduced after breaching of natural barriers.